2011
DOI: 10.1186/1475-2891-10-133
|View full text |Cite
|
Sign up to set email alerts
|

Relative validation of the KiGGS Food Frequency Questionnaire among adolescents in Germany

Abstract: BackgroundThe aim of this study was to determine the relative validity of the self-administered Food Frequency Questionnaire (FFQ) "What do you eat?", which was used in the German National Health Interview and Examination Survey for Children and Adolescents (KiGGS 2003-2006).MethodsThe validation was conducted in the EsKiMo Nutrition Module, a subsample of KiGGS. The study population included 1,213 adolescents aged between 12 and 17. A modified diet history interview DISHES (Dietary Interview Software for Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 46 publications
7
56
0
2
Order By: Relevance
“…The main limitation of estimated records is the higher participant burden due to multiple-day recording which may discourage completion [60,61]. Despite careful preparation of the food record as an easy-to-carry booklet and provision of portion aids to facilitate accurate recordings, we acknowledge that misreporting may still occur given the limited motivation and possible poor portion size estimation among adolescents [62,63]. …”
Section: Discussionmentioning
confidence: 99%
“…The main limitation of estimated records is the higher participant burden due to multiple-day recording which may discourage completion [60,61]. Despite careful preparation of the food record as an easy-to-carry booklet and provision of portion aids to facilitate accurate recordings, we acknowledge that misreporting may still occur given the limited motivation and possible poor portion size estimation among adolescents [62,63]. …”
Section: Discussionmentioning
confidence: 99%
“…A positive family history of CVD was defined as a diagnosis of coronary heart disease, angina, heart attack, congenital heart disease or stroke in first-degree male relative of child and/or parent under the age of 55 or first-degree female relative of child and/or parent under the age of 65 [11]. Information on childhood nutrition habits was gathered by means of an established standardized food frequency questionnaire (“What do you eat?”, kindly provided by the Robert Koch Institute, Berlin, Germany) [12]. Childhood nutrition was subsequently categorized as unfavorable, neutral or favorable for further analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The development of the FFQ is described in detail elsewhere [35]. The FFQ was validated against the modified dietary history method DISHES (Dietary Interview Software for Health Examination Studies) and showed fair to moderate ranking validity for food intake amounts for most of the food items (Spearman correlation coefficients from .35 to .69 with most values above .50) [22]. The FFQ included questions on the average food consumption frequency, as well as the average consumed portion size, for 45 food items in the last few weeks.…”
Section: Dietary Assessmentmentioning
confidence: 99%
“…This can be accomplished by investigating a priori-defined healthy eating indices, which are based on a judgement of appropriateness of the food intake. Previously, we analyzed the association between such dietary indices and biomarkers in the same population [22]. For the current study, we applied principal component analysis (PCA), which is a data driven method and results in patterns that more objectively represent prevailing eating habits of the population.…”
Section: Introductionmentioning
confidence: 99%